Seasonal Amplitude of Water Storage Variations of the Yangtze–Huai Plain Lake Group: Implicaion for Floodwater Storage Capacity - Song, Lijuan; Song, Chunqiao; Zhan, Pengfei; Chen, Tan; Liu, Kai; Jing, Haitao (Frontiers in Environmental Science, 2022)
Lakes are of significant importance in regulating floods and providing water sources. The seasonal water storage variations for the plain lake group in the Yangtze–Huai River Basin (YHRB) are significant for alleviating flood pressure and regulating runoff. However, to date, the seasonal amplitude of lake water storage variations and its capacity of buffering floodwater in the YHRB is not quantified well and remains to be investigated comprehensively. To advance the understanding of such a critical scientific issue, the water level data of the plain lake group (area>100 km2, 29 lakes) in the YHRB is collected from multi-source data between 1990 and 2020. Using lake inundation area obtained from Global Surface Water and water level variations, water storage dynamics for the plain lake group are quantified. Furthermore, this study also uses the Gravity Recovery and Climate Experiment (GRACE) products to analyze the terrestrial water storage anomalies (TWSA) in the whole basin. The results indicate that the seasonal amplitude of water level change and water storage variation of the plain lake group are 2.80 ± 0.71 m and 37.38 ± 14.19 Gt, respectively. Poyang and Dongting Lakes, two lakes that maintain the natural connection with the Yangtze River, have the most substantial seasonal amplitude in the hydrological situation. The amplitude in water level and water storage in Poyang Lake is 9.53 ± 2.02 m and 14.13 ± 5.54 Gt respectively, and that in Dongting Lake is 7.39 ± 1.29 m and 7.31 ± 3.42 Gt respectively. The contribution of seasonal variation of water storage for large plain lakes to TWSA in the YHRB is approximately 33.25%, fully reflecting these lake's imperative position in the YHRB. This study is expected to enhance the scientific understanding of the seasonal hydrologic regime for the large lakes in the YHRB and contribute to the management of flood risks and water resources in East China.